2018
DOI: 10.32674/jis.v7i3.295
|View full text |Cite
|
Sign up to set email alerts
|

A Developmental Sequence Model to University Adjustment of International Undergraduate Students

Abstract: The current study proposes a Developmental Sequence Model to University Adjustment and uses a multifaceted measure, including academic, social and psychological adjustment, to examine factors predictive of undergraduate international student adjustment. A hierarchic regression model is carried out on the Student Adaptation to College Questionnaire to examine theoretically pertinent predictors arranged in a developmental sequence in determining adjustment outcomes. This model accounted for over 60% of the varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Conversely, students who have good social interaction and social support will have lower psychological problems than students who are not supported by their social environment [27]. Social support is an essential factor affecting student performance in higher education [10].…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, students who have good social interaction and social support will have lower psychological problems than students who are not supported by their social environment [27]. Social support is an essential factor affecting student performance in higher education [10].…”
Section: Resultsmentioning
confidence: 99%
“…Included were problems of adjustment to a new culture, discrimination, financial concerns, ill-health, accommodation, food selection, social isolation; and lack academic success (Berry & Kostovcik, 1983;Church, 1982;Klineberg & Hull, 1979;Mickle, 1985). While there are exceptions (De Moissac et al, 2020), more recent research confirms the continued presence of these issues (Calder et al, 2016;Chavoshi et al, 2018;Fletcher & Stren, 1989;Ge et al, 2019;Travares, 2021;Wang, 2016;Westwood & Barker, 1990;Zhang & Noels, 2021;Zhou & Zhang, 2014).…”
Section: Experiences and Outcomesmentioning
confidence: 98%
“…When proceeding in this fashion, I recognized that adjustment is a multidimensional concept. It can include measures of state of mind, interaction, and living up to personal expectations and those of others (Chavoshi et al, 2018).…”
Section: Adjustment To Universitymentioning
confidence: 99%
“…According to Lee et al (2019), an additional study revealed that while local students do not experience loneliness or homesickness in their host colleges, overseas students do. Furthermore, research indicates that international students' adjustment problems are significantly influenced by factors such as gender, country of origin, and grade/year in school (Chavoshi et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%